Communication, Education and social movements online: New Imaginaries, old utopias - Cortés-González, Pablo; García-López, Marcial; Cortés-González, Alfonso (My University, 2014)
Due to the Internet arrival, the Social Movements, alternatives and critics, have considered it as a new scene capable to renew the traditional ways of intervention and collective action. Besides it is open the possibility to outdo the activism atomization of the social movements, organizing them in a global strategy, articulated upon nodes of local intervention. There is a renewed illusion, due to this inclusion of social movements in the Internet, understood as a new pedagogical tool for the organization, the debate, the broadcast and the social mobilization, which wake up old social utopias, that nowadays they are proposed as real and feasible utopias. This way we regard that the role of the citizenship, as a participant in the political power, could be replaced by a mere contract of enjoyment of goods and services in the Internet worldwide (Pérez Luño, 2004). So, the individual may find satisfied the technological utopia which includes the promise of social change. The tension generated by these to powers seems to be granting a privilege to an instrumental use of New Technologies in the transformation processes that promote the social movements. This way we may misunderstand the managing of utopias with simple strategies of online communication and education. Therefore, it is needed to overflow (in a metaphorical way) that instrumental interpretation of the Internet to release deep structural transformations and new imaginaries related to the utopia of a free communication and education media, at the service of a democratical society development.
Keywords: Acción social; Internet; Acción social online; Movimientos Sociales; Educomunicación; Comunicación para el cambio social; Utopías